Cardiac CT angiography: Comprehensive assessment of patient suspected coronary artery disease - Sarinya Puwanant (2018)
Coronary artery disease is the leading cause of mortality and morbidity worldwide. Although coronary angiography is currently a gold standard for diagnosis of coronary artery disease, some patients are of concern regarding small but not negligible risk of complications and discomfort of the procedure. In recent years, cardiac computerized tomographic angiography (CTA) is an attractive non-invasive modality for evaluation of chest pain in patients suspected to have coronary artery disease. The authors report a 61 year-old-man with a history of hypertension and hypercholesterolemia who presented with exertional angina pectoris for 3 weeks. Cardiac CTA was performed and revealed a severely stenotic lesion at the proximal left anterior descending coronary artery (LAD) with left ventricular ejection fraction of 53% and hypokinesia of anteroseptal and apical wall. The patient then was planned and underwent percutaneous coronary interventional procedure. This case highlights the utility of comprehensive information from cardiac CTA as a modality for coronary interventional procedure planning.